Comparison of effectiveness of aminoglycosides and cephalosporins in gram-negative rods - Vrbová, E; Uxová, M; Výmola, F (Czechoslovak medicine, 1986)
Aminoglycosides and cephalosporins belong among antimicrobials with a pronounced effect on most gram-negative rods. In vitro susceptibility and resistance to gentamicin, tobramycin, amikacin, netilmicin, cefoxitin, cefotaxime, cefsulodin, cefoperazone in Klebsiella pneumoniae, Enterobacter spp., Proteus mirabilis, Escherichia coli and Pseudomonas aeruginosa was tested by the quantitative dilution micromethod. Selected, highly susceptible strains of the above species were furthermore compared for minimal inhibitory concentration (MBC) and minimal bactericidal concentration (MBC) values. Aminoglycosides tended to be the most effective drugs for susceptible strains. In view of their relative toxicity possibly optimal combinations of individual aminoglycosides with individual cephalosporins are discussed.
Keywords: aminoglykosidy; Gram-Negative Bacteria; gramnegativní bakterie; antibakteriální látky; Aminoglycosides; kombinovaná farmakoterapie; Anti-Bacterial Agents; cefalosporiny; Drug Therapy, Combination; Cephalosporins